Design and construction of “Bamboo Cubic” facade with laminated bamboo lumber - Xue, Xin; Zhou, Wenjing; Sayed, Usama; Feng, Zixian; Li, Haitao; Li, Yipeng; Huang, Zhiyong; Ashraf, Mahmud; Lorenzo, Rodolfo (Sustainable structures, 2023)
This paper presents the design and construction of the facade renovation project ("Bamboo Cubic" project) of Huangqiao Square in Shaowu City, Fujian Province, China. In this project, the structural form and cross-sectional dimensions were determined using a combination of manual and finite element analysis to meet relevant regulations. Once the structural form was confirmed, primary structural components such as the foundation, the column base, and the connection between frame elements were designed to comply with design requirements. Innovative connections were used to install a unique curved design, which required curved LBL members to be prefabricated with precision. The total height of the LBL bamboo frame part is 16.86 m. This project clearly showed that engineered bamboo can be used both as a structural primary member as well as for aesthetic purpose. Use of steel and LBL frames in the "Bamboo Cubic" facade project highlighted the prospect of future hybrid construction.